2022
DOI: 10.3389/fonc.2022.879828
|View full text |Cite
|
Sign up to set email alerts
|

Current Researches on Nanodrug Delivery Systems in Bladder Cancer Intravesical Chemotherapy

Abstract: Bladder cancer is one of the most common malignant tumors in urinary system. Intravesical chemotherapy is a common adjuvant therapy after transurethral resection of bladder tumors. However, it has several disadvantages such as low drug penetration rate, short residence time, unsustainable action and inability to release slowly, thus new drug delivery and new modalities in delivery carriers need to be continuously explored. Nano-drug delivery system is a novel way in treatment for bladder cancer that can increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 97 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Given the poor prognosis of advanced bladder cancer and the limited effectiveness of current chemotherapeutics, intensive research continues on new pharmacological agents that may be promising in future targeted therapies for bladder cancer [ 37 , 38 , 39 , 40 , 41 ]. One such compound, sorafenib, is an oral multitarget inhibitor of various receptor tyrosine kinases involved in tumor progression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the poor prognosis of advanced bladder cancer and the limited effectiveness of current chemotherapeutics, intensive research continues on new pharmacological agents that may be promising in future targeted therapies for bladder cancer [ 37 , 38 , 39 , 40 , 41 ]. One such compound, sorafenib, is an oral multitarget inhibitor of various receptor tyrosine kinases involved in tumor progression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial progress in the field of nanotechnology and the constant development and improvement of drug delivery systems have led to the emergence of many nanoplatforms for the diagnosis and treatment of bladder cancer. Micro-and nanocarriers for the delivery of chemotherapeutic agents (doxorubicin, cisplatin, pirarubicin, paclitaxel, and others), gene tools (small interfering ribonucleic acid, RNA), immunotherapy agents (BCG), and photodynamic drugs for bladder cancer are being developed [ 5 , 11 , 12 , 24 , 25 ].…”
Section: Colloidal Nano- and Micro-sized Delivery Systemsmentioning
confidence: 99%
“…The challenge consists in delivering an effective dose in the bladder together with minimization of the undesired biodistribution, which could increase side effects. Different strategies have been developed to improve drug efficacy and tolerability [ 5 , 9 , 10 , 11 , 12 ], and intravesical delivery can be considered as the preferred mode of drug delivery, although the pharmacodynamics of administered drugs is impaired by urinary production and excretion. Conventional treatment for NMIBC include (1) transurethral resection of bladder tumor (TURBT), in which malignant tissue is removed with an electrocautery device during cystoscopy; (2) intravesical immunotherapy with the Bacillus Calmette–Guérin (BCG) vaccine or chemotherapeutic drugs and surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies indeed showed an increase in drug accumulation and a decrease in cytotoxic side effects in tumor tissues, some of which have been already in clinical trials 4 . Nevertheless, the major of additional materials may inevitably bring out adverse impacts, such as, the drug loading capacities were relatively low, most delivery materials which were just as excipients may cause added toxicities or undesirable immune response 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%